The role of allergy in the etiopathogenesis of idiopathic sudden sensorineural hearing loss - Keles, Erol; Sapmaz, Emrah; Godekmerdan, Ahmet (Springer, 2013)
To evaluate the role of allergy in the etiopathogenesis of sudden hearing loss using cytokine profile, allergic parameters, and lymphocyte subgroups, a total of 31 patients aged between 30 and 62 years (mean age: 42.48 +/- A 15.86 years) with the diagnosis of sudden hearing loss were enrolled in the study between 2008 and 2011. The control group comprised 30 age-matched adult subjects accepted as clinically healthy individuals living in the same region with comparable socioeconomic parameters. The patient and the control group were questioned for history of allergy. Lymphocyte subgroups in the peripheral blood were evaluated using Becton-Dickinson monoclonal CD4, CD8, CD19, and CD23 antibodies. In the patient and control groups, the levels of IFN- gamma, IL4, IL10, and total IgE were measured and compared between the groups. Skin test was used for detection of inhaler allergens in the patient and the control groups, and specific IgE tests were performed using the RAST method for food allergens. The Spearman's rho correlation, the unpaired t test, the Mann-Whitney U test, and the Shapiro-Wilk test were used to determine the differences between the groups. The limit for statistical significance was p < 0.05. When the patient and the control group were compared, the differences between CD4, CD23, IL4, IL10, and IgE were statistically significant. On analyses of the patients' serum samples, strongly positive correlations were determined between IgE and CD23, IL10, IL4; IL4 and IL10, CD23, CD4; IL10 and CD23, CD4 (Spearman rho, p = 0.000), while a weakly positive correlation was found between IgE and CD4 (Spearman rho, p = 0.020). A correlation between IFN-gamma and CD4 was weakly negative (Spearman rho, p = 0.040). The total IgE levels were estimated to be above the normal reference ranges (0-100 IU/ml) in 25.8 % of the cases in the patient group. History of allergy was found in 61.9 % of the patients. The results of this study substantiate the role of allergy in the etiopathogenesis of sudden hearing loss. We think that during the diagnostic work-up of these patients allergy should be interrogated seriously, necessary tests should be performed, and allergy should be considered in the decision-making process of the treatment of sudden hearing loss.
Keywords: Allergy; Cytokines; Lymphocyte subgroups; Sudden hearing loss